ENVIRONMENTAL APPROACH IN HIGHER EDUCATION: METHODOLOGICAL ASPECTS - Bratko, Mariya (Continuing Professional Education: Theory and Practice, 2023)
This articledealing with the theoretical background of the environmental approach in higher education is grounded on the idea of the methodological approach as the conceptual basis of educational activity that defines its strategy and tactics, regulates its tools, resources, and has a two-tier structure that includes methodological and technological levels. The analysis of the basic concepts of the approach — environment, learning environment, educational environment of higher education — is done. The structure and functions of the educational environment of higher education are found. It is concluded that the environmental approach in higher education is a system of controlling subject’s actions within the educational environment of a higher educational institution aimed at acquiring characteristics of such an environment that would allow implementing the polystructural educational function successfully. The author considers the educational environment not only the conditionbut also the factor of formation and development of a future specialist’s competence